“Modelos pedagógicos de la educación general básica y su relación con el ajuste curricular 2016 en la escuela Agustín Albán, Guápulo, Pujilí, circuito 05d04c09_11, periodo 2022_2023.” - Tigasi Pilaguano, Jenny Marisol (2023)
The Education must train children in integrity, innovative and critical values, where the teacher is guided by models such as cognitivism, sociocultural and constructivism, eliminating the traditionalism where the teaching-learning process is based on rote, limiting to the student to participate and give an opinion, therefore, when replacing it, cognitive abilities and skills are developed based on significant knowledge where the contents are adjusted to the educational and social reality, since learning is essential to forge attitudes and ideals. The objective is to analyze the importance of the application of pedagogical models and their relationship with the 2016 curricular adjustment in the teaching-learning process, with the purpose of establishing which pedagogical model is applied in the "Agustín Albán" Basic Education School. For which, the methodology used is the inductive-deductive method to collect true information and analyze the results obtained through reflection, therefore, the inquiry was carried out with 10 teachers and 70 randomly selected students to identify which approach is prioritized in the study Establishment, for this, the survey was used as a technique and the questionnaire as an instrument. The results are activities that contribute to learning where it was evidenced that the majority of educators apply the constructivist model and ideas of the new school, since they incorporate strategies, resources and methodologies in order to promote autonomous work, interactive material, recreational activities and teamwork, to build their own learning through experience, inquiry, curiosity and motivation, in addition to assessing and prioritizing educational needs, since education is flexible and dynamic, so that models are a fundamental instrument for addressing the problems that exist at the different educational levels, while helping to establish links between the teacher and the student.